HIV infection is associated with elevated biomarkers of immune activation in Ugandan adults with pneumonia. - Richard J Wang; Julia Moore; Daniela Moisi; Emily G Chang; Patrick Byanyima; Sylvia Kaswabuli; Emmanuel Musisi; Ingvar Sanyu; Abdulwahab Sessolo; Rejani Lalitha; William Worodria; J Lucian Davis; et al. (PLoS ONE, 2019)
Introduction Pneumonia is an important cause of morbidity and mortality in persons living with human immunodeficiency virus (HIV) infection. How immune activation differs among HIV-infected and HIV-uninfected adults with pneumonia is unknown. Methods The Inflammation, Aging, Microbes, and Obstructive Lung Disease (I AM OLD) Cohort is a prospective cohort of adults with pneumonia in Uganda. In this cross-sectional analysis, plasma was collected at pneumonia presentation to measure the following 12 biomarkers: interleukin 6 (IL-6), soluble tumor necrosis factor receptors 1 and 2 (sTNFR-1 and sTNFR-2), high sensitivity C-reactive protein (hsCRP), fibrinogen, D-dimer, soluble CD27 (sCD27), interferon gamma-inducible protein 10 (IP-10), soluble CD14 (sCD14), soluble CD163 (sCD163), hyaluronan, and intestinal fatty acid binding protein. We asked whether biomarker levels differed between HIV-infected and HIV-uninfected participants, and whether higher levels of these biomarkers were associated with mortality. Results One hundred seventy-three participants were enrolled. Fifty-three percent were HIV-infected. Eight plasma biomarkers-sTNFR-1, sTNFR-2, hsCRP, D-dimer, sCD27, IP-10, sCD14, and hyaluronan-were higher among participants with HIV infection, after adjustment for pneumonia severity. Higher levels of 8 biomarkers-IL-6, sTNFR-1, sTNFR-2, hsCRP, IP-10, sCD14, sCD163, and hyaluronan-were associated with increased 2-month mortality. Conclusions As in other clinical contexts, HIV infection is associated with a greater degree of immune activation among Ugandan adults with pneumonia. Some of these are also associated with short-term mortality. Further study is needed to explore whether these biomarkers might predict poor long-term outcomes-such as the development of obstructive lung disease-in patients with HIV who have recovered from pneumonia.